ANALISIS GAYA BAHASA PADA PUISI “ARITMIA” KARYA WIRA NAGARA - Juliyanto Sugihartono; Kosasih Ismail; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
In writing poetry each author has a style of language or technique that is his trademark. Some are accustomed to regular rhyme patterns, some are using rhetorical language styles. On this occasion the researcher wanted to find out what language style was used by Wira Nagara, in his poem entitled "Arrhythmia". So from that the researchers agreed to use structuralism-semiotic analysis research methods. From the data that has been analyzed this study obtained several conclusions. The style of language used in the poem "Artimia" is the style of the language antithesis, personification, alliteration, aconance and hyperbole. Of the total there are 22 language styles, consisting of 9 personifications, 2 antithesis, 6 alliterations, 4 asonances, and 1 hyperbole.